The Digital Transformation of Trust: How AI is Reshaping the Doctor-Patient Relationship - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into clinical practice represents one of the most profound shifts in modern healthcare. Beyond its technical ap...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care